Harmonic analysis of shear deformable orthotropic cracked plates using the Boundary Element Method (2012)
In this work, the modal and harmonic analysis of orthotropic shear deformable cracked plates using a direct time-domain Boundary Element Method formulation based on the elastostatic fundamental solution of the problem is presented. The Radial Integration Method was used for the treatment of domain integrals involving distributed domain applied loads and those related with inertial mass forces. Numerical examples are presented to demonstrate the efficiency and accuracy of the proposed formulation. © 2012 Elsevier Ltd. All rights reserved.